Societal Consequences of Modern Hybrid Warfare in Political-Economic and Institutional Discourse - Grytsenko, A.; Burlai, T.; Borzenko, O. (BUKETOV BUSINESS REVIEW, 2023)
Object: to reveal the features of the societal approach to the study of the modern hybrid war consequences, a striking example of which is the Russian invasion of Ukraine in February 2022, based on the study of the reflection of changes in social reality in the unity of political-economic, sociological and institutional discourses. Methods: ascension from the abstract to the concrete; dialectical; logical-historical; fractal method of institutional economics; structural-functional and world-systems analysis. Findings: the current Russian-Ukrainian war has clear signs of a modern hybrid war generated by the globallocal hybrid system “peace — war” and combines a whole complex of means: military-political, economic, cybernetic, etc. On the basis of the combination of political-economic, sociological (in a broad sense) and institutional discourses, it is substantiated that the main components of the “peace — war” hybrid system from the point of view of the societal relations transformation are: armed-military, financial-economic and informational-spiritual components. It is shown that through the channels of world perception and positioning they lead to changes in behavioural patterns, through which the response of the actors is carried out, changing the already changing reality. This leads to the closure of changes in social reality through the behaviour of subjects on themselves, gives integrity and acceleration to societal processes. Conclusions: the feature of the societal approach is revealed only on the basis of a combination of politicaleconomic (which opens up the possibility of tracing chains of cause-and-effect relationships), sociological in a broad sense (allowing you to look at society as a whole in the unity of its components and measure them) and institutional (giving the key to understanding changes in rules and norms of social life) approaches. This feature consists, in contrast to the social approach (fixing the structural and functional structure of social reality), in the study of social transformations, which actualizes the problems of interaction and reflexivity of social structures and functions. In the conditions of martial law, the role of the trust institution as a defining and integral construct of the socio-economic system’s institutional architectonics, embodied both in trust in the state and power structures, and in trust in new institutions born of hybrid war. The societal approach opens up the possibility of a new look at the problems of the Ukrainian post-war reconstruction, taking into account both the objective logic of social transformations and the need to increase social activity in institutional transformations that involve the formation of a new development model in the European socio-economic space.